2021
DOI: 10.1371/journal.pone.0251108
|View full text |Cite
|
Sign up to set email alerts
|

Association between short-term exposure to sulfur dioxide and carbon monoxide and ischemic heart disease and non-accidental death in Changsha city, China

Abstract: Background To investigate the effects of short-term exposure to sulfur dioxide (SO2) and carbon monoxide (CO) in the central and southern China areas on ischemic heart disease (IHD) and non-accidental deaths. Method We investigated the associations between short-term exposure to SO2 and CO in a city in south-central China and IHD and non-accidental death using a time-series design and generalized additive models with up to a 5-day lag adjusting for day of the week, temperature, air pressure, wind speed, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
1
6
4
Order By: Relevance
“…Although Liu et al (2018) , Li et al (2018) , Bell et al (2009) , and Motessadi Zarandi et al (2022) adjusted other pollutants by only two pollutant models and did not use multiple-pollutant models, the same as our findings, their results were robust to controlling for other pollutants. Unlike our study, the result of Xu et al (2021) did not remain robust when adjusted for SO 2 .…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Although Liu et al (2018) , Li et al (2018) , Bell et al (2009) , and Motessadi Zarandi et al (2022) adjusted other pollutants by only two pollutant models and did not use multiple-pollutant models, the same as our findings, their results were robust to controlling for other pollutants. Unlike our study, the result of Xu et al (2021) did not remain robust when adjusted for SO 2 .…”
Section: Discussioncontrasting
confidence: 99%
“…In the current study, in a time-series framework, we investigated the association between the ambient CO and hospitalizations for CVDs, using Poisson’s regression or negative binomial regression models and applying the data extracted from the CAPACITY study for patients aged 18 years or more. The mean concentration of CO in our study was 4.5 ± 2.3 mg/m 3 , which was a little higher than the recommended standard of 4 mg/m 3 ( Evangelopoulos et al, 2020 ) and higher than that in other studies such as Vahedian et al (2017) and Xu et al (2021) .…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…On the contrary, females were more sensitive to NO 2 and SO 2 in our study, which is in line with several previous studies [ 14 , 30 , 41 , 42 ]. A study conducted in southern China showed that the risk of IHD death from short-term exposure to SO 2 was greater in women than in men [ 20 ]. A recent study in Canada reported that females were at higher risks of IHD hospitalization from NO 2 exposure than males [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, some of these studies were limited to a particular district or a hospital [ 19 ] in Wuhan, and the populations of these studies may not represent the entire population. In addition, recent large-scale studies that focused solely on the health hazards of particulate matter (PM 2.5 and PM 10 ) [ 5 ], and the relationship of ambient NO 2 and SO 2 with the risk of IHD hospitalization have not been adequately investigated in China [ 20 ]. Therefore, a study on the association between air pollutants (both particulate matter and gaseous pollutants) and IHD hospitalization based on the entire population of Wuhan is needed to better understand the actual impact of ambient air pollution problems in central China.…”
Section: Introductionmentioning
confidence: 99%